2011
DOI: 10.1007/s12011-011-9194-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin against Sodium Fluoride-Induced Toxicity in Rat Kidneys

Abstract: In the present study, the protective effect of curcumin against sodium fluoride-induced nephrotoxicity was evaluated in rats. Renal injury was induced by daily administration of 600 ppm sodium fluoride in drinking water for 1 week. One week before the administration of fluoride, the animals selected as study group were given curcumin (10 and 20 mg/kg body weight, intraperitoneally). After 1 week, lipid peroxidation level, activities of superoxide dismutase, catalase, and level of glutathione in kidney homogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…These pathophysiological changes were accompanied by a decrease in serum nitrite/nitrate and by downregulation of renal SOD activity, suggestive of high oxidative stress and impairment of antioxidant defences. Earlier studies (3,24,25) have established that NO defi ciencyrelated excessive production of ROS by renal parenchymal cells, resident macrophages, infi ltrating infl ammatory cells, and persistent oxidative stress can impair renal antioxidant defence through inactivation of antioxidant enzymes. Similar changes have been reported in cardiac and/or aortic tissues of L-NAMEtreated rats (14,26).…”
Section: Discussionmentioning
confidence: 99%
“…These pathophysiological changes were accompanied by a decrease in serum nitrite/nitrate and by downregulation of renal SOD activity, suggestive of high oxidative stress and impairment of antioxidant defences. Earlier studies (3,24,25) have established that NO defi ciencyrelated excessive production of ROS by renal parenchymal cells, resident macrophages, infi ltrating infl ammatory cells, and persistent oxidative stress can impair renal antioxidant defence through inactivation of antioxidant enzymes. Similar changes have been reported in cardiac and/or aortic tissues of L-NAMEtreated rats (14,26).…”
Section: Discussionmentioning
confidence: 99%
“…The volume was made up to 300 µL with water before incubation at 37°C for 1 h. The color reaction was developed by adding 300 µL of sodium dodecyl sulphate (8.1%) to the reaction mixtures containing fractions (Nabavi et al, 2012a).…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…However, recent studies estimated that about 20% of pharmaceuticals and 30-40% of agrochemicals are organofluorines. 1 Fluoride-containing compounds are also commonly used in household products and office (e.g., dental products, refrigerants, and fire extinguishers). 2 Prolonged intake of fluoride or excessive consumption results in fluorosis, leading to a progressive degenerative disease, often characterized by dental mottling and skeletal dysfunctions including crippling deformities, osteoporosis, and osteosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Prolonged intake of fluoride or excessive consumption results in fluorosis, leading to a progressive degenerative disease, often characterized by dental mottling and skeletal dysfunctions including crippling deformities, osteoporosis, and osteosclerosis. 1 Several studies revealed that fluoride intoxication in the hippocampus of the rat brain can lead to the degeneration of neuronal systems and an alteration of the oxidantantioxidant balance in other organs and tissues. 3 The kidney has a prominent role in fluoride metabolism as 50-80% of fluoride is removed via urinal excretion.…”
Section: Introductionmentioning
confidence: 99%